2010
DOI: 10.1177/1098214010381780
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Roles and Heterogeneous Practices: Understanding the Adoption and Uses of Nonprofit Performance Evaluations

Abstract: Evaluating the performance of nonprofit organizations has been of growing importance for the last several decades. Although there is much good that can come out of self-improvement, there is substantial heterogeneity within the sector that calls into question the usefulness of ''across the board'' evaluation tools. In this article, the authors assess nonprofit evaluation practices, at both the organizational and the programmatic levels. Through a multitheoretical framework, the authors explore the extent to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 31 publications
5
65
0
Order By: Relevance
“…From an institutional theory perspective, performance measurement is a largely symbolic (or ceremonial) practice to acquire institutional legitimacy by conforming to institutional norms (e.g., Eckerd & Moulton, 2010;Lee & Nowell, 2015;Modell, 2009;Roy & Seguin, 2000;Yang, 2009). In our study, we found that coercive, mimetic, and normative pressures have positive and significant influences on the adoption of outcome measurement.…”
Section: Institutional Factorsmentioning
confidence: 55%
See 2 more Smart Citations
“…From an institutional theory perspective, performance measurement is a largely symbolic (or ceremonial) practice to acquire institutional legitimacy by conforming to institutional norms (e.g., Eckerd & Moulton, 2010;Lee & Nowell, 2015;Modell, 2009;Roy & Seguin, 2000;Yang, 2009). In our study, we found that coercive, mimetic, and normative pressures have positive and significant influences on the adoption of outcome measurement.…”
Section: Institutional Factorsmentioning
confidence: 55%
“…Institutional theory holds that organizations seek to obtain legitimacy because it enhances organizational growth and survival by providing means to acquire various resources such as capital, human resources, technology, and networks (Aldrich & Fiol, 1994;Dart, 2004;Eckerd & Moulton, 2010;Meyer & Rowan, 1977;Zimmerman & Zeitz, 2002;Zucker, 1987). In this regard, Dart (2004) argues that institutional theory is "built around the concept of legitimacy" (p. 415).…”
Section: Institutional Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Performance measurement and evaluation is an important and increasingly demanding practice in the third sector (Reed & Morariu, 2010, Benjamin, 2008Carman, 2007, Eckerd & Moulton, 2011Charities Evaluation Service, 2008;Bagnoli & Megali, 2010). There is a focus on how to improve the measurement and evaluation of third sector organisations through multi-dimensional frameworks (Bagnoli & Megali, 2010) and balanced scorecards (Kaplan, 2001) and through linkages to strategic decision making (LeRoux & Wright, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A diversity of approaches can generate debate about the design of particular performance measurement and evaluation techniques and the relative merits of the different types of information that they produce (Charities Evaluation Service, 2008;Reed & Morariu, 2010;Waysman & Savaya, 1997;Eckerd & Moulton, 2011). A common disagreement in such debates concerns the claim that case studies and stories can be 'subjective' whereas performance indicators and statistics are more 'objective' (e.g., see discussion in Jacobs et al, 2010;Wallace et al, 2007;Abma, 1997;Porter & Kramer, 1999).…”
Section: Introductionmentioning
confidence: 99%